Image steganography for hiding videos (International Journal of Engineering and Computer Science, 2015)
Steganography is going to gain its importance due to the exponential growth and secret communication of potential computer users over the internet. It can also be defined as the study of invisible communication that usually deals with the ways of hiding the existence of the communicated message. Generally data embedding isachieved in communication, image, text, voice or multimedia content for copyright, military communication, authentication and many other purposes. In image Steganography, secret communication is achieved to embed a message into cover image (used as the carrier to embed message into) and generate a stegoimage(generated image which is carrying a hidden message). In proposed we are embedding video file in the image for secret sharing of data and also keen on obtaining the same quality of image after decoding.This paper intends to give an overview of to hide videos inside image, its uses and techniques. In this project video hidden inside the image for which video get compressed and stored inside the image.features are extracted before encryption for effective re-construction